Impact of mannose‐binding lectin 2 gene polymorphisms on disease severity in noncystic fibrosis bronchiectasis in children. Issue 5 (2nd March 2020) - Dogru, Deniz; Polat, Sanem E.; Tan, Çağman; Tezcan, İlhan; Yalçın, Sıddıka S.; Utine, Eda; Oğuz, Berna; Yaz, İsmail; Emiralioğlu, Nagehan; Hızal, Mina; Yalçın, Ebru; Özçelik, Uğur; et al.
Abstract: Background: Mannose‐binding lectin (MBL) is a complement protein involved in the innate immune system, and is associated with some chronic respiratory diseases including noncystic fibrosis (non‐CF) bronchiectasis in adults. The aim of this study was to investigate the frequency of MBL2 gene polymorphisms in children with non‐CF bronchiectasis, and the effect of MBL deficiency on disease severity. Methods: Fifty children with non‐CF bronchiectasis (bronchiectasis group) and 50 healthy controls (control group) were included. The demographic findings, number of acute pulmonary exacerbations in the previous year, airway cultures, pulmonary function tests, and radiologic scores of the bronchiectasis group were recorded. DNA extraction was performed in both groups and MBL2 gene polymorphisms in codons 52, 54, 57 in exon 1 and H/L, Y/X in the promoter region were studied using real‐time polymerase chain reaction. Haplotypes were made by genotypes, and MBL serum expression was classified according to the genotypes in the literature. Results: The bronchiectasis group consisted of 23 (46%) patients with primary ciliary dyskinesia, 5 (10%) with primary immunodeficiency diseases, and 22 (44%) with idiopathic bronchiectasis. There were no statistically significant differences between the bronchiectasis and control groups in terms of allele and genotype frequencies of polymorphisms in codons 52, 54, 57 in exon 1 and promoter H/L. However, the YX heterozygote genotype was more frequent in the control group (82%) compared with the bronchiectasis group (50%) ( P  = .002). The frequency of patients with intermediate serum MBL expression genotype was higher in the bronchiectasis group (20%) than in the control group (0%) ( P  = .001). In the bronchiectasis group, there were no significant differences in growth, annual pulmonary exacerbation rates in the last year, pulmonary function tests, radiologic scores, and microbiologic findings between low, intermediate, and high‐expressing genotypes. Conclusions: In children with non‐CF bronchiectasis, MBL genotype was different from healthy controls. MBL deficiency associated only with MBL genotype was not related to disease severity in this group of patients.